The employment of digital tools in the study of Ancient Thrace (Research Announcements "Heritage BG", 2025)
The employment of digital tools in the study of Ancient Thrace can enhance our understanding of the region. The vast volume of analog data available underscores the need for interconnected datasets via repositories. Digitizing various data types, including archaeological finds, literary works, and inscriptions, promotes scholarly collaboration. Moreover, the study of Thrace, a region rich in history and mythology, also benefits from research with GIS tools that enable quantitative analyses, study of people and object diffusion, trade networks, and landscape exploration. These technological advancements revolutionize archaeological research, potentially driving economic growth and influencing cultural policies. References:Avramidou, Amalia, Despoina Tsiafaki. 2022a. Preliminary Results of the Research Project Attic Pottery in Thrace. In: The Proceedings of the 13th International Congress of Thracology “Ancient Thrace: Myth and Reality”, Kazanlak, September 3-7, 2017, volume 1, Sofia, 35-44.Avramidou, Amalia, Despoina Tsiafaki. 2022b. Attic Kraters and Pelikai from Ancient Thrace. In: Greek and Etruscan Vases: Shapes and Markets: Panel 5.15, (Archaeology and Economy in the Ancient World: Proceedings of the 19th International Congress of Classical Archaeology, Cologne/Bonn 2018, Band 34), ed. Dimitris Paleothodoros. Heidelberg, 57-75.Banev, Guentcho. forthcoming. I érevna tis attikís graptís keramikís sti Voulgaría: aparkhés, poría kai sinisphorá. Mía episkópisi tis vivliographías me aphormí to érgo AtticPOT. – Mare Ponticum.Bikakis, Nikos et al. 2023. Exposing geospatial cultural heritage content in map-based applications. In: Proceedings of the 6th International Workshop on Big Data Visual Exploration and Analytics co-located with EDBT/ICDT 2023 Joint Conference (March 28-31, 2023), Ioannina, GR (BigVis), eds. George Fletcher, Verena Kantere. Available at: https://ceur-ws.org/Vol-3379/BigVis2023_700.pdf.Chioti, Eirini, Amalia Avramidou, Despoina Tsiafaki. 2019. The AtticPOT project – Attic PO(ttery in) T(hrace). – BeJA, 9/2, 293-294.Damyanov, Margarit. 2022. Attic painted pottery on the West Pontic Coast: Across the gaps. In: Tsiafaki et al. 2022, 288-306.Giouli, Voula et al. 2022a. From mythos to logos: A bilingual thesaurus tailored to meet user’s needs within the ecosystem of cultural tourism. In: Dictionaries and Society. Proceedings of the XX EURALEX International Congress, September 7, 2022, eds. Annette Klosa-Kückelhaus, Stefan Engelberg, Christine Möhrs, Petra Storjohann. Mannheim, 625-634.Giouli, Voula et al. 2022b. Placing multi-modal, and multi-lingual Data in the Humanities Domain on the Map: the Mythotopia Geo-tagged Corpus. In: Proceedings of the 13th Conference on Language Resources and Evaluation (LREC 2022), Marseille, 20-25 June 2022, eds. Nicoletta Calzolari et al. Paris, 2859-2864.Graser, Anita. 2016. Learning QGIS. Birmingham-Mumbai.Iliopoulou, Sofi. 2015. Arkhaía Zóni IIIa. To nekrotaphío. Taphiká éthima kai praktikés. Komotini.Iliopoulou, Sofi, Chrysafenia Pardalidou. 2022. Attikí graptí keramikí apó tin arkhaía Zóni. In: Tsiafaki et al., 2022, 228-244.Michailidou, Natasa. 2022. I attikí keramikí “sta khéria” tis psiphiakís tekhnoloyías: to érgo AtticPOT se evrítero plaísio. In: Tsiafaki et al. 2022, 38-56.Michailidou, Natasa et al. forthcoming. AtticPOT: a borderless approach for studying Attic painted pottery in ancient Thrace. In: Computer applications and quantitative methods in Archaeology (CAA), June 14-18, 2021 (online event).Michailidou, Natasa, Vassilis Evangelidis, Despoina Tsiafaki. 2020. ARENA EDU: Creating Digital Educational Content for Twenty First Century Archaeological Visits. In: Education VIA Culture: An International Conference on the Applications of Cultural Heritage in Education, December 18-20, 2020, Thessaloniki, Greece (through Zoom).Mourthos, Yiannis, Despoina Tsiafaki. 2022. Contextualizing rare shapes of Athenian Kerameikos from coastal and inland Thrace (6th–4th c. BC): an approach through the AtticPOT repository. – BeJA 12/2: 217-243.Papadopoulos, Stratis. 2022. Sistimatiki anaskaphi Pistírou: i próti pentaetía. In Ídia i mními yinámeni parón – To arkhaioloyikó érgo ton ephorión arkhaiotíton katá ti khronikí período 2011-2019, ed. Eleni Kotsou. Athens, 458-462.Şahin, Reyhan. 2016. Red-figure Pottery of the 4th Century BC from Ainos in Thrace: The Final Phase of the Classical Tradition in Eastern Thrace. In: Traditions and Innovations. Tracking the Development of Pottery from the Late Classical to the Early Imperial Periods. Proceedings of the 1st Conference of lARPotHP, Berlin, November 2013, 7th-10th, IARPotHP 1, eds. Sarah Japp, Patricia Kögler. Wien, 2016, 329-340.Tsiafaki, Despoina. 1998. I Thráki stin attik^ ikonograph^a tou 5ou aiona p. Kh. Proseng^- sis stis skhésis Athínas kai Thrákis. Komotini.Tsiafaki, Despoina. 2016. Ancient Thrace and Thracians through the Athenian eyes. – Thracia 21: 261-282.Tsiafaki, Despoina. 2022. AtticPOT. H Athinaïkí parousía stin arkhaía Thráki (6os – 4os ai. p. Kh.). In: Tsiafaki et al. 2022, 57-76.Tsiafaki, Despoina, Κostantia Amoiridou. forthcoming. Prótes paratirísis yia tin proimi isigméni keramik^ tis aiyaiakis Pist^rou. In Aiyaiak^ P^stiros, ed. Stratis Papadopoulos.Tsiafaki, Despoina et al. 2020. I arkhaioloyikí érevna sti Tháso mésa apó to psiphiakó apothetírio ARENA. In: 8o Simpósio Thasiakón Meletón, 12-14 Oktovríou 2019 (Thasiaká 20). Kavala, 443-463.Tsiafaki, Despoina et al. 2022. AtticPOT: Attic Painted Pottery in Ancient Thrace (6th – 4th Century BC). New Approaches and Digital Tools. Xanthi.Tsiafaki, Despoina et al. 2023. Mythical Journeys in Eastern Macedonia and Thrace. Xanthi.Tsiafaki, Despoina et al. forthcoming. “I parousía tis attikís keramikís stin arkhaía Thráki mésa apó to érgo AtticPOT”. In: To Arkhaioloyiko Érgo sti Makedon^a kai sti Thráki, 33i Epistimonikí Sinántisi (2019-2020), 22-24 Aprilíou 2021. Thessaloniki.Tsiafaki, Despoina et al. forthcoming. As far as Attic vases go: studying the presence of Athenian Kerameikos in ancient Thrace. In: European Association of Archaeologists (EAA) Annual Meeting, Budapest, 31 August- 3 September 2022.Tsiafaki, Despoina, Vassilis Evangelidis. 2006. GIS as an Interpretative Tool in Greek Archaeological Research. In: Proceedings of the GIS Research UK 14th Annual Conference, GISRUK 2006, 5th-7th April, 2006, eds. G. Priestnall, P. Aplin. UK, 328-333.Tsiafaki, Despoina, Vassilis Evangelidis. 2022. Exploring Rivers and Ancient Settlements inAegean Thrace through Spatial Technology. In: The Riverlands of Aegean Thrace: Production, Consumption and Exploitation of the Natural and Cultural Landscapes | River Valleys and Regional Economies: Panel 2.4 | Panel 2.7, ed. Euridike Kefalidou. Heidelberg, 45-61. Tsiafaki, Despoina, Natasa Michailidou. 2019. Ways to Cope with the Scientific ARENA: Taking the Results of Archaeological Research a Step Further. In: Proceedings of the 23rd International Conference on Cultural Heritage and New Technologies Held in Vienna, Austria November 2018, 1-9.Tsiafaki, Despoina, Natasa Michailidou, Eirini Chioti. 2020. AtticPOT: éna psiphiakó ergalío yia tin erminía tis parousías attikon ang^on stin arkhaia Thraki. In: 3o Panellínio Sinédrio Psiphiopíisis Politistikís Klironomiás – EuroMed 2019, Athína, 25-27 Septemvríou 2019. Αθήνα, 156-167.Tsiafaki, Despoina, Yiannis Mourthos, Natasa Michailidou. forthcoming. Old data new tools: 4th century lekythoi in ancient Thrace through AtticPOT. In: International Workshop “Greek Pottery of the 4th cent. B.C. New Data from the Field”, 29 November 2021, École Française d’Athènes.Vacalopoulou, Anna et al. 2023. Mythological Itineraries Along the Western Silk Road: Finding Myths in Visits to Eastern Macedonia and Thrace Today. In: Cities’ Vocabularies and the Sustainable Development ofthe Silkroads, SRSTDCH 2021, eds. S. Kostopoulou, G. Herrera-Franco, J. Wood, K. Al-Kodmany. Cham, 139-153.
Keywords: Athena RC; repositories; Attic pottery; mythology; GIS; networks; landscape